Determination of the Distribution of Uranium in Glass Solidified Samples by Secondary Ionization Mass Spectrometry - XIE Wei-yi; SHEN Yan; LI Li-li; ZHAO Yong-gang (Yankuang ceshi, 2016)
Glass solidification is a common method for curing highly radioactive waste liquid. This method has the advantages of high resistance to chemical corrosion, and good radiation, thermal, and mechanical stability. However, the disadvantage is the decline of resistance to water leaching so that the reliability of the result needs to be confirmed by an anti-leaching test. Using Secondary Ionization Mass Spectrometry (SIMS) to analyze the composition distribution and leaching behavior of radioactive components (such as uranium) in the solid glass is a method for evaluating the ability of resistance to leaching of solidified glass. The simulated glass solidified sample was tested by SIMS and the results are reported and discussed in this paper. Carbon was used as the coating material during vacuum evaporation coating on the surface of the sample in order to overcome the poor conductivity of the sample. The isotopic composition of natural uranium is about 7.3‰. And the ratio of 235U/238U in the prepared solid glass is 7.9‰±0.395‰. The research indicates that the method can determine the measurement of the isotopic abundance of uranium and directly show its distribution. This method can provide technical support for the study of the leaching behavior of radioactive elements in solidified glass samples.